Investigating the role of the strong field ligands in [FeFe] hydrogenase: spectroscopic and functional characterization of a semi-synthetic mono-cyanide active site. Issue 37 (19th August 2022) - Lorenzi, Marco; Gellett, Joe; Zamader, Afridi; Senger, Moritz; Duan, Zehui; Rodríguez-Maciá, Patricia; Berggren, Gustav
Abstract : Cyanide to carbonyl exchange in semi-synthetic [FeFe] hydrogenases: exploring the role of the strong field ligands of the active site and their interaction with the protein matrix via spectroscopy and electrochemistry. Abstract : Artificial maturation of hydrogenases provides a path towards generating new semi-synthetic enzymes with novel catalytic properties. Here enzymes featuring a synthetic asymmetric mono-cyanide cofactor have been prepared using two different hydrogenase scaffolds. Their structure and reactivity was investigated in order to elucidate the design rationale behind the native di-cyanide cofactor, and by extension the second coordination sphere of the active-site pocket. Surprisingly, the choice of host enzyme was found to have a dramatic impact on reactivity. Moreover, the study shows that synthetic manipulations of the active-site can significantly increase inhibitor tolerance, as compared to native [FeFe] hydrogenase, while retaining the enzyme's native capacity for reversible catalysis.